Comparison of outcome of compression dressing for two days Vs seven days after varicose surgery - Noor ul Ain; Rana Sohail Ahmad; Chaudhry, Zainab; Mohammad Sohail Asghar; Ameer Afzal; Mohammad Musaab; Hafiz Syed Zaigham Ali Shah (Journal of the Pakistan Medical Association, 2022)
Incompetence of the great saphenous vein (GSV) is a global issue and the most prevalent cause of chronic venous disease of the leg. Clinical manifestations range from moderate to severe, including tiredness, heaviness, and irritation, as well as hyperpigmentation and leg ulcers. A study was conducted to address this controversy,(1) i.e. to determine the outcome of compression dressing after varicose vein surgery in terms of postoperative pain, on the Surgical floor, of Mayo Hospital, Lahore, from October 1, 2020, to April 1, 2021. A total of 60 patients with Primary varicose veins were enrolled in this study, fulfilling the inclusion criteria after obtaining approval from the ethical committee of the hospital. The patients were divided in two groups. Group A wore compression dressing for two days after surgery and Group B wore compression dressing for seven days after surgery. All the patients received 1gm Paracetamol I/V eight hourly followed by tablet Paracetamol 500mg P/O eight hourly. Then the outcome of compression dressing was analysed in the form of mean postoperative pain. The mean pain score was assessed on one week. Data were entered in SSPS v23.0. Stratification of pain score was done against age, gender, and grades of varicose veins. A comparison of the two groups was done by applying a t-test. A p-value of 0.05 was considered significant. Prescribing compression stockings for longer than two days after Trendelenburg’s procedure leads to reduced pain and improved physical function during the first week after treatment. Keywords: Trendelenburg’s procedure, Great saphenous vein, Compression stockings.